PENGARUH PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - Kristian Bondon (Jurnal Ekonomi STIEP, 2022)
ABSTRACT The purpose of this study was to determine the effect of government spending (indirect spending and direct spending) on ​​economic growth in Berau District. The samples used in this study are the Berau District Government LRA time series for 2011-2020 and BPS Berau publication data in Figures for the 2012-2021 time series. The analytical tools used are: normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis, correlation coefficient, coefficient of determination, t test, and F test. The results of the study concluded that: 1). Government spending through indirect spending has a partially significant effect on economic growth in Berau District. Evidenced by the results of the t test where t-count < - t-table (-4.383 < -2.365) and the significance value (Sig.) is smaller than the probability value (0.003 < 0.05); 2). Government spending through direct spending partially has a significant effect on economic growth in Berau District. Evidenced by the results of the t test where t-count > t-table (2.416 > 2.365) and the significance value (Sig.) is smaller than the probability value (0.046 <0.05); and 3). Government spending through indirect spending and direct spending has a significant simultaneous effect on economic growth in Berau District. This is evidenced by the results of the F test where F-count > F-table (10.139 > 4.74) and the significance value (Sig.) is smaller than the probability value (0.009 <0.05).